Banking competition and economic growth: an empirical study on the OECD countries - Hung, Kwai Him Cedric (2018)
Theoretically, increase in banking competition can provide consumers better accesses to bank loans due to the decrease in costs of financing which can boost the growth. However, with the presence of asymmetric information, mixed results have been found on the effect of banking competition on economic growth. Some suggest that some degree of market power in the banking sector are required to reduce the problem caused by asymmetric information. The banks are more willing to engage a better lending relationship with the clients and provide more loans to the firms which can promote the sectorial growth. This paper review some of the previous literature on related issues and employs panel data to examine the effect of banking competition (proxied by the Lerner index and the Boone indicator) on economic growth with the data of the OECD countries in the years of 2011-2016. No significant relationship between banking competition and economic growth are found within the OECD sample period which may suggest that the effect of banking competition on economic growth are more obvious in the long-run since only data of seven years are included in this paper due to insufficient data on bank financial data.